Breaking state-centric shackles in the WHO: Taiwan as a catalyst for a new global health order - LIN, Ching-Fu (Institutional Knowledge at Singapore Management University, 2020)
After World War II, states established World Health Organization (WHO), recognizing that “the health of all peoples is fundamental to the attainment of peace and security.” This aspiration, embedded in GlobalHealth governance, introduces a paradox vis-à-vis the WHO’s state-centric institutional design. Though Taiwan alerted the WHO to potential human-to-human transmission in the early stage of the pandemic, its participation in the WHO remains limited, contrasting the WHO’s goal of health for all peoples sharply against its outdated emphasis on statehood and power politics.This Essay critically assesses how and why state-centric international health governance neither delivers its goal to “promote and protect the health of all peoples” nor accommodates the complexity of international politics, and explores new venues allowing a pluralist membership structure that better serves the WHO’s promise. We propose two ways of reinventing global health governance. The first approach is to reform within the WHO, which involves the amendment to Article 8 of the WHO Constitution. This can release the WHO from the shackles of state-centrism and move towards a new institutional design suitable for global health governance in the twenty-first century. The second approach is to go beyond the state-centric international organization by focusing more on the role of trans-government networks in reconstructing the new global health order in the post- COVID-19 era. Overall, our two-pronged approach aims at inclusiveness of global health governance, which will hopefully solicit and steer new actors, processes, and outputs in the re-established WHO or any new institutional settings.